Globalization and the new media content through information communication technology: a threat? / Dr. Mokhtar Muhammad - Muhammad, Mokhtar (Dr.) (Faculty of Communication and Media Studies (FCMS), 2004)
Globalization as defined by John Tomlinson (1991), refers to the rapidly developing process of complex interconnections between societies, cultures, institutions and individuals worldwide. It is also the process which involves the compression of time and space, shrinking distance through a dramatic reduction in the time taken either physically or represently to cross them, so making the world seem smaller and in a certain sense bringing human beings closer to one another. Bit it is also a process which 'stretches' social relations, removing the relationships which govern on everyday lives from local context to global ones.